2022
DOI: 10.1007/s42844-022-00069-7
|View full text |Cite
|
Sign up to set email alerts
|

The Wither or Thrive Model of Resilience: an Integrative Framework of Dynamic Vulnerability and Resilience in the Face of Repeated Stressors During the COVID-19 Pandemic

Abstract: During the first 2 years of the COVID-19 pandemic, empirical efforts in the psychological sciences have been unequivocally focused on understanding the psychosocial impact on resilience and vulnerability. While current empirical work is guided by different existing theoretical models of resilience and vulnerability, the emerging datasets have also pointed to a necessity for an update of these models. Due to the unique features and developments specific to the current pandemic such as the occurrence of repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 186 publications
(173 reference statements)
0
4
0
Order By: Relevance
“…In line with recent models of resilience and vulnerability processes in the pandemic context 21 , IU is expected to predict psychopathology, and ER difficulties and CCF are considered to modulate the impact of this factor on the trajectory of psychopathology. In line with these theoretical models, studies have vouched for a mediating effect of ER difficulties in the relationship between IU and psychopathology 23 , 67 , and another study has shown that different levels of CCF moderate the relation between IU and psychopathology 61 .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In line with recent models of resilience and vulnerability processes in the pandemic context 21 , IU is expected to predict psychopathology, and ER difficulties and CCF are considered to modulate the impact of this factor on the trajectory of psychopathology. In line with these theoretical models, studies have vouched for a mediating effect of ER difficulties in the relationship between IU and psychopathology 23 , 67 , and another study has shown that different levels of CCF moderate the relation between IU and psychopathology 61 .…”
Section: Introductionmentioning
confidence: 79%
“…Despite the progress that has been made in understanding risk factors that aggravate the impact of the COVID-19 pandemic, there is much that remains to be understood about the interplay between key risk and protective factors for mental health. A recent conceptual framework proposed that the pandemic has challenged people in at least three ways, namely dealing with uncertainty, regulating negative emotions, and flexibly adapting to changing contexts 21 . Difficulties in these domains may engender mental health issues 22 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, few of these longitudinal studies showed that levels of mental health problems tended to increase with each measurement occasion [26,27], which is in line with cumulative risk models [28][29][30]. This points to a unique feature of the COVID-19 pandemic, such that the longer individuals were under strict lockdown conditions, the worse their mental health became, leading to what can be termed a pandemic fatigue effect [31].…”
Section: Introductionmentioning
confidence: 83%
“…Thus far, however, most studies have investigated time-stable moderators of intervention responses, such as personality traits, socio-demographic variables, dispositional mindfulness and response styles, or baseline symptom levels [8,10,13]. However, the prevailing models of resilience conceptualize resilient mental wellbeing as a dynamic process 2 of 13 of stress recovery that evolves over time in response to encountered life stressors, and not as a mere reflection of specific time-stable psychological aspects [14,15]. Consequently, it can be extrapolated that dynamic stress recovery profiles, derived from an ecologically valid assessment of reactivity to naturalistic stressors, might be more uniquely suited to predicting individual differences in intervention gains since they index the individual capacity for plasticity in response to dynamic contexts, explaining who shows responsivity in a mental training context [16].…”
Section: Introductionmentioning
confidence: 99%